Fertility following intrauterine administration of Tinidazole and Ciprofloxacin combination in repeat breeding crossbred cows - DHILLON, N S; DHALIWAL, G S; JAND, S K (The Indian Journal of Animal Reproduction, 2005)
It is well established that bovine uterus provides an environment, which is conducive for the growth of both aerobes and anaerobes that act synergistically to cause bacterial endometritis. Therefore, treatment strategies demand that drugs effective against both aerobes and anaerobes should be used. In the present study 15 repeat breeding cross bred cows having uterine infection were selected on the basis of aerobic and /or anaerobic bacterial growth in the uterine swabs. All these cows were treated with tinidazole and ciprofloxacin combination for 3 consecutive days. At subsequent oestrus uterine swabs were again taken and cultured for both aerobic and anaerobic bacteria and artificial insemination was done at the same oestrus. Both aerobic and anaerobic infection were cleared completely in 9 cows while the clearance was partial in 5 cows i.e. elimination of either aerobes or anaerobes after treatment. One cow did not respond to treatment in terms of clearance of infection. Overall, six (40%) cows became pregnant within 3 inseminations following the treatment, of them 5 cows belonged to totally cleared group. First service pregnancy was achieved in only 2 cows that had sterile uterine environment after the treatment. Bacteriological cure rate after treatment was better in case of obligate anaerobes (90%) as compared to aerobes (67%). Also treatment was not effective in clearing E. coli infection. To conclude, though ciprofloxacin and tinidazole combination was effective against mixed infection of aerobes and anaerobes in vitro, results in terms of pregnancy establishment were not encouraging.